Penerapan Metode Moving Average Pada Bengkel XYZ Berbasis Web Menggunakan Metode Waterfall - Gunawan H C Sibuea; Febry P J Sibuea (STMIK Banjarbaru, 2025)
The digital era has brought significant transformation to various business sectors, including the automotive repair industry. XYZ Workshop faces challenges in managing fluctuations in service demand and spare parts requirements. To address these issues, this research develops a web-based stock prediction system using the Moving Average method and the Waterfall software development model. The Moving Average method is employed to analyze historical data and accurately forecast stock needs, assisting the workshop in efficient restocking planning. The web-based system provides real-time access to stock information, facilitating quick and well-measured decision-making. The Waterfall model ensures that system development is conducted systematically, from requirements analysis to testing. The research results indicate that the application of the Moving Average method on the web-based system effectively improves stock management efficiency, reduces the risk of stockouts or overstocking, and enhances operational flexibility. This system can serve as a reference for other workshops in optimizing inventory management.Keywords: Prediction System; Moving Average; Stock Management; Waterfall. AbstrakEra digital telah membawa transformasi signifikan pada berbagai sektor bisnis, termasuk industri perbengkelan. Bengkel XYZ menghadapi tantangan dalam mengelola fluktuasi permintaan layanan dan kebutuhan suku cadang. Untuk mengatasi masalah tersebut, penelitian ini mengembangkan sistem prediksi kebutuhan stok berbasis web menggunakan metode Moving Average dan model pengembangan perangkat lunak Waterfall. Metode Moving Average digunakan untuk menganalisis data historis dan meramalkan kebutuhan stok secara akurat, membantu bengkel melakukan perencanaan restock yang efisien. Sistem berbasis web memberikan akses real-time terhadap informasi stok, memudahkan pengambilan keputusan yang cepat dan terukur. Model Waterfall memastikan pengembangan sistem dilakukan secara sistematis, mulai dari analisis kebutuhan hingga pengujian. Hasil penelitian menunjukkan bahwa penerapan metode Moving Average pada aplikasi web efektif meningkatkan efisiensi pengelolaan stok, mengurangi risiko kekurangan atau kelebihan stok, serta meningkatkan fleksibilitas operasional. Sistem ini dapat menjadi rujukan bagi bengkel lain dalam optimalisasi manajemen persediaan.Kata Kunci: Sistem Prediksi; Moving Average; Manajemen Stok; Waterfall.